2013
DOI: 10.1371/journal.pone.0082266
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Plastid Marker Variation: Can Complete Plastid Genomes from Closely Related Species Help?

Abstract: Rapidly evolving non-coding plastid regions (NCPs) are currently widely used in evolutionary biology especially in plant systematic studies where NCPs have become one of the most commonly used tools in clarifying species relationships. Currently, the generally small amount of sequence variation provided by NCPs compared to nuclear regions makes plastid phylogeny reconstruction challenging at the species-level, especially so in species rich clades such as Solanum with c. 1,200 species. Previous studies have est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 57 publications
(77 reference statements)
3
38
0
Order By: Relevance
“…A few NC‐cpDNA regions stand out as being the most likely to contain high levels of variability at the inter‐ and intraspecific levels, even though this study (Figs. 2–4) and a body of literature (Mort et al, 2007; Shaw et al, 2007; Särkinen and George, 2013) reinforces the observation that there is no universally best NC‐cpDNA. That said, screening what are known to be, on average, the fastest evolving regions is a good starting point for molecular investigations of new groups (Cires et al, 2012; Fior et al, 2013).…”
Section: Discussionmentioning
confidence: 52%
“…A few NC‐cpDNA regions stand out as being the most likely to contain high levels of variability at the inter‐ and intraspecific levels, even though this study (Figs. 2–4) and a body of literature (Mort et al, 2007; Shaw et al, 2007; Särkinen and George, 2013) reinforces the observation that there is no universally best NC‐cpDNA. That said, screening what are known to be, on average, the fastest evolving regions is a good starting point for molecular investigations of new groups (Cires et al, 2012; Fior et al, 2013).…”
Section: Discussionmentioning
confidence: 52%
“…The non-coding spacer trn S- trn G provided more interspecific distance (0.0268) than the two coding fragments ( rbc L and mat K), but trn S- trn G provided lower species discrimination (33.3%). However, the debate regarding the use of non-coding regions in DNA barcoding is ongoing due to unreliable alignment of sequences with very high variation (Särkinen and George, 2013). In addition, some authors suggest that indel regions of non-coding DNA sequences provide important phylogenetic information and species discrimination power for some of the group, e.g., Taxus (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the top 10 markers listed with less than 900 bp have been occasionally used in phylogenetic studies across disparate plant lineages with variable resolution, but never in cacti. The clpP gene is usually employed with its introns Lam et al 2016), and the psbB-clpP intergenic spacer has been increasingly reported as useful marker (Loera et al 2012;Särkinen and George 2013;Prince 2015). The intergenic spacer ycf4-cemA has been used for phylogenetic studies in Asteraceae and Poaceae genera Ekenas et al 2007) and the rps2 gene in Orobanchaceae and…”
Section: Phylogenetically Informative Regionsmentioning
confidence: 99%